TRADISI MAANTA KATUPEK DI NAGARI SIMAWANG KECAMATAN RAMBATAN KABUPATEN TANAH DATAR MENURUT HUKUM ISLAM - Nur Azizah; Farida Arianti (UIN Mahmud Yunus Batusangkar, 2023)
This research examines how to apply the customs of maanta katupek in Nagari Simawang, Rambatan District, TanahBackground Regency for Islamic law and how Islamic law is studied for the application of maanta katupek in Nagari Simawang, Rambatan District, Tanah Datar Regency. The purpose of this review is to identify and explain how to apply the customs of maanta katupek in Nagari Simawang, Rambatan District, Tanah Datar Regency and to analyze Islamic legal ideas for the implementation of the customs of Maanta Katupek in Nagari Simawang, Rambatan District, Tanah Datar Regency. The research method used is field research, to obtain data from supervised cases. The method of gathering information used is through monitoring and debriefing with KAN leaders, niniak mamak, and husband and wife companions who do not practice the maanta katupek customs. Processing of information was attempted by descriptive qualitative. The results of the research is that after carrying out a marriage or offering sincerity in Nagari Simawang, Tanah Datar Regency, there are customary provisions that must be carried out, namely the customs of maanta katupek, maanta katupek, which is a routine of maanta katupek which is delivered by the husband to the wife's house if the companion carries out walimah , if these customs have not been carried out until the marriage for the husband and wife's companion in a legal custom in Nagari Simawang, Rambatan District, Tanah Datar Regency, it is listed as having an arranged marriage. The conclusion of this research can be concluded that the customs of Maanta Katupek are traditions passed down from generation to generation by residents in Nagari Simawang. The limitation in this research is that researchers only carry out research in Simawang Nagari. suggesting connection research to be a challenge in formulating problems.